Implementasi Perda Qanun di Aceh terhadap Anak Dibawah Umur yang Melakukan Perjudian - Permatasari, Dewi Cahyani Nigita; Nugrono, Bastianto; Supolo, Supolo (Fakultas Syariah INSURI Ponorogo, 2022)
Law Number 11 of 2007 concerning the Government of Aceh is the legal order in the legal system and national legislation system. In Article 1 number 21 of Law Number 11 of 2006, it is determined that